2001
DOI: 10.1074/jbc.m101380200
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycan Structures from the Major Glycoproteins of Pigeon Egg White

Abstract: N-Glycans from major glycoproteins of pigeon egg white (ovotransferrin, ovomucoid, and ovalbumins) were enzymatically released and were reductively aminated with 2-aminopyridine, separated, and structurally characterized by mass spectrometry and a three-dimensional mapping technique using three different columns of high performance liquid chromatography (HPLC) (Takahashi, N., Nakagawa, H., Fujikawa, K., Kawamura, Y., and Tomiya, N. (1995) Anal. Biochem. 226, 139 -146). Twentyfive major N-glycan structures, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…When P-fimbriated E. coli were allowed to accumulate on pigeon ovalbumin, a Gal-1,4-Gal-presenting glycoprotein (27,28), for 5 min at shears ranging from 0.01 to 4.3 pN/m 2 ( Fig. 7A), no shear threshold was seen, and accumulation decreased with increased shear.…”
Section: Shear Stress Enhances P-fimbrial E Coli Adhesion To Gal-14mentioning
confidence: 99%
“…When P-fimbriated E. coli were allowed to accumulate on pigeon ovalbumin, a Gal-1,4-Gal-presenting glycoprotein (27,28), for 5 min at shears ranging from 0.01 to 4.3 pN/m 2 ( Fig. 7A), no shear threshold was seen, and accumulation decreased with increased shear.…”
Section: Shear Stress Enhances P-fimbrial E Coli Adhesion To Gal-14mentioning
confidence: 99%
“…As expected, major proteins from all samples were visualized in the range of 30-80 kDa, although the mobility patterns varied from species to species. Different properties of avian egg white proteins, attributable to amino acid sequences and glycosylations in a species-specific manner, might have manifested in the Representative N-glycan structures of ovalbumins from chicken (36 -38) and pigeon (12,13). Specificity of lectins (Con A, RCA-I, and GS-I) and anti-P 1 mAb for the detection of oligosaccharides were also indicated.…”
Section: Lectin͞antibody Staining Of Avian Egg White Glycoproteinsmentioning
confidence: 99%
“…We recently showed that pigeon (Rock Dove, Columba livia) express Gal␣1-4Gal (galabiose) antigens attached on glycoproteins from egg white (12,13) and serum (14), and analyzed their N-glycan structures (Fig. 1).…”
mentioning
confidence: 99%
“…A rather unexpected finding from the studies of pigeon ® E.coli E.coli α egg white N-glycans was that the NeuAc-Gal linkages in pigeon egg whites are α(2-6)-, which is the linkage found in humans, rather than α(2-3)-found in most other birds (8). Indeed, pigeons are found to be more resistant to avian influenza than other birds (41).…”
Section: F Galabiose and Sialyl-gal Linkages In Pigeon Egg Whitementioning
confidence: 99%
“…However, little is known about how the multivalency of such epitopes (i.e., clustering of glycan chains) will enhance the binding affinity. We fortuitously found that the pigeon egg white glycoproteins contain Neu5Acα(2-6)Gal linkage rather than Neu5Acα(2-3)Gal commonly found in other avian species (8). A subsequent report (9) showed that pigeons indeed are more resistant to avian flu.…”
mentioning
confidence: 96%